(untitled) (Jahangirnagar University Journal of Biological Sciences, 2024)
A study was conducted to compare the morpho-reproductive traits of twenty two genotype of Petunia in order to select superior and sustainable genotypes for commercial cultivation in Bangladesh during winter 2021-22. Thirteen qualitative and quantitative characters viz. stigma type, leaf shape, plant height (cm), number of branches, number of effective branches, days to flower initiation, number of flowers, duration of flowers, flowering duration, plant longevity, number of stamens, stamen length (cm) and petiole length (cm) were observed during the study period. The findings found that all morpho-reproductive traits differed significantly amongst the genotypes investigated, with the exception of the stamens, which were five in number. Highest quantitative variation was observed in days to flower initiation and longevity of the plants. Glow picotee blue showed the superior plant height (29.33 cm). Deep salmon had the shortest time to bloom initiation (52 days). Maximum number of flowers was recorded from ultra purple star (50) followed by ultra crimson star (49.67) while the duration of the flowers was maximum (6.67 days) in opera supreme white, prism pink, ultra burgundy star and ultra purple star. Opera supreme white had the longest flowering time (69.67 days). Whereas ultra purple star, ultra crimson star and ultra rose star had the longest lifespan (111 days). The genotypes deep salmon, ultra purple star, ultra red star, ultra rose star, opera supreme white, dreams midnight, and prism pink are recommended for commercial cultivation based on their overall morpho-reproductive performance. Jahangirnagar University J. Biol. Sci. 12(1 & 2): 23-33, 2023 (June & December)